Mineral content of bread enriches with unripe saba banana flour - M. A. Shareenie; Mansoor Abdul Hamid; Hasmadi Mamat; H.A. Jaharul (Faculty of Science and Natural Resources, 2020)
The macro and micro-element contents of bread with different composition (%) of unripe Saba banana flour (USBF) were determined by Inductively Coupled Plasma Optical Emission, (ICPOES). Calcium (Ca), Potassium (K), Magnesium (Mg) and Sodium (Na) in bread were established as the macro-element. Mg contents of bread change from 28.53 to 63.53 mg/100g and the highest Mg content was found at bread with the highest USBF substituted. While K contents of bread increased from 322.65 to 551.76 mg/100g, it is identified as the highest concentration major element found in all bread samples, and the concentration increases significantly (p0.05) in the micro-element Selenium (Se) and Copper (Cu) contents of bread. Manganese (Mn) contents of bread were determined from 1.17 to 2.20 mg/100g and found higher (p<0.05) compared to the controlled group. Zinc (Zn) and Iron (Fe) contents of bread ranged from 1.16 to 2.41 mg/100g and 0.51 to 0.75 mg/100g, respectively. The addition of 10% fortified USBF significantly increased (p<0.05) K and Mg content and significantly decreased (p<0.05) the concentration of Ca and Zn in bread. Overall findings indicated that USBF could to be utilized as an alternative functional ingredient to improve the essential minerals in bread alongside showed a good approach to exploit the local crop.